Matrix–fiber interfacial debonding in soft composite materials: Cyclically behavior modeling and microstructural evolution. (15th May 2022) - Mansouri, M.R.; Fuchs, P.F.; Baghani, M.; Schuecker, C.
Abstract: It is apparent from the literature that the matrix–fiber mechanical interaction, as a result of interfacial adhesive bonds at the interface, significantly contribute to the macroscopic constitutive response of hyperelastic fiber-reinforced materials. This study bridges the degradation of macroscopic mechanical properties to the microscopically visible matrix–fiber interfacial debonding for cyclically deformed soft composites. The present work is an initial attempt to model matrix–fiber interfacial debonding in the context of pseudoelasticity by evaluating inelastic phenomena such as discontinuous Mullins softening and residual strain due to matrix damage, fiber rupture, and matrix–fiber interfacial debonding. The pseudoelastic model is based on hyperelastic strain energy functions consisting of two damage variables for each matrix, fiber, and matrix–fiber mechanical interaction. Each material and damage parameter is characterized independently by performing a comprehensive set of monotonic loading and cyclic tensile tests, respectively. Furthermore, finite element analysis is implemented using a user-defined subroutine, and the computationally calculated results are compared with the experimental data.